PERCONTOHAN PEMANFAATAN BETON RINGAN UNTUK PINTU RUMAH TINGGAL DI KECAMATAN KASEMEN KELURAHAN BENDUNG SERANG - JAWA BARAT - Damayanti, Julia; Nelfia, L. Oksri; Okvianti Irlan, Ade; F Kuswanda, Giraldi; Maulani, Mustamina (Universitas Trisakti, 2024)
In the construction of residential buildings such as simple houses, the existence of a door is certainly a basic requirement that must exist. One of the criteria of a good door is weather resistance by having a good door leaf material, not easily weathered and also not easy to shrink (expand or bend). Generally, doors are made using wood materials because they add aesthetic value to the building construction with a variety of grain patterns and unique textures from wood. But on the other hand, the forest current condition as a source of wood production is increasingly concerning. This also has an impact on good quality wood which is difficult to obtain and increasingly expensive. Technological developments in the field of construction materials provide an alternative from the usage of door leaf materials which majority using wood materials to switch to alternative materials usage such as steel, glass, PVC and lightweight concrete. The usage of lightweight concrete began to be widely used as a door leaf material because it is more resistant to weather, has a stable size and is not weathered by termites. From an economical standpoint, the price of lightweight concrete doors is relatively cheaper compared to the price of wooden doors with equivalent specifications. The purpose of this Community Service activity is to increase public understanding, to provide knowledge about alternative wooden door as well as providing examples of alternative materials, namely lightweight concrete doors with wood texture and environmental friendliness. The used method consists of several stages, namely socialization of the development of the construction material technology, installing lightweight concrete panel doors in the Bendung Serang sub-district and showing the installation process and making of lightweight concrete panel doors through videos and photos showcase. The benefits specifically for the people in the Bendung sub-district is that the innovation of this lightweight concrete panel door material is acceptable. This community service activity has educated the public about technological innovations in construction material such as alternative materials.